Nivel de contaminación acústica en las empresas de produccion de balsa ubicadas en el cantón Quevedo, provincia de Los Ríos, 2015 - Marín Loor, Rodolfo Antonio (2015)
This research was conducted in the parish San Carlos Quevedo Canton province of Los Rios in 2015. Its main objective was to determine the level of noise pollution in the production of raft companies located in the canton Quevedo. To perform measurements of internal and external noise:  For internal measurements that are generated due to the process of manufacture of balsa, inspections will be carried out in situ of the jobs of the three companies, to identify noise peaks.  For external measurements, measured by the four sides of the three companies. For measurements of internal noise 17 points were established in the three companies, which were taken at 08:00 am and afternoon 14:00 pm, in the days of 23 to 27 March this year and external noise it was made at the same time, from March 28 to April 6. According to the study of internal noise measurements in the three companies it is determined that the noise level in the company Balsablock exceeds the maximum permissible limits, making it necessary to develop an action plan to mitigate the high levels of noise. For measurements of external noise 12 points were established in the three companies, determining that the more noise occurs on the west side of Balsablock due to the compressors of briguetas and the noise that comes from the same company Balsablock